2012
DOI: 10.1007/s11739-012-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the modified MEDS, MEWS score and Charlson comorbidity index in patients with community acquired sepsis in the emergency department

Abstract: Sepsis is one of the most important causes of morbidity and mortality in patients presenting to the emergency department. SIRS criteria that define sepsis are not specific and do not reflect the severity of infection. We aimed to evaluate the ability of the modified mortality in emergency department sepsis (MEDS) score, the modified early warning score (MEWS) and the Charlson comorbidity index (CCI) to predict prognosis in patients who are diagnosed in sepsis. We prospectively investigated the value of the CCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…Four studies were performed in emergency departments [22][23][24]27 ; two were in internal medicine. 25,26 Three studies were relatively small in size (<400 participants), 23,24,27 one was moderate (n=535) 26 and two included more than 1000 participants. 22,25 Five studies used the MEWS system, one study used the National Early Warning Score (NEWS), a slight variation.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were performed in emergency departments [22][23][24]27 ; two were in internal medicine. 25,26 Three studies were relatively small in size (<400 participants), 23,24,27 one was moderate (n=535) 26 and two included more than 1000 participants. 22,25 Five studies used the MEWS system, one study used the National Early Warning Score (NEWS), a slight variation.…”
Section: Resultsmentioning
confidence: 99%
“…To compare disease severity in different sepsis subgroups, we calculated the MEWS, consisting of several vital signs, and the AVPU score in all patients, as well as the modified Mortality in Emergency Department Sepsis (mMEDS) score [20, 21], which incorporates several risk factors (terminal illness, tachypnea/hypoxia, septic shock, platelet count <150,000/mm 3 , age >65 years, lower respiratory tract infection, nursing home residency, altered mental state). A contemporary version of the Charlson Comorbidity Index (CCI) was used to compare chronic disease burden [22].…”
Section: Methodsmentioning
confidence: 99%
“…However, several meta-analyses of qSOFA scores have shown that these scores had a poor sensitivity for predicting in-hospital mortality [10][11][12][13][14]. Early warning scores [15,16], a tool for identifying hospitalized patients at risk of deterioration, have been proposed for predicting hospital mortality in those with suspected sepsis in the ED [7,[17][18][19][20]. However, Hamilton et al reported that the early warning scores were not accurate in predicting sepsis mortality in the ED (67% of sensitivity and 60% of specificity) [21].…”
Section: Introductionmentioning
confidence: 99%